An integrated model of the thermoregulatory and respiratory systems of the human body. (July 2020) - Albuquerque, C.; Yanagihara, J.I.
Abstract: This work aims to develop a mathematical model for computing the distribution of temperature, O2, and CO2 in the human body, depending on the ambient conditions. The body is divided into segments, including layers of tissues and blood compartments, where mass and energy balances are applied. The inclusion of O2 and CO2 transfer mechanisms throughout all segments and tissues of the human body is one of the great novelties of this work. It also includes the exothermic metabolic reactions in the tissues, the transportation of O2 and CO2 by the blood, and the energy exchanged with the environment through the skin and by ventilation. The model also includes the regulation of metabolism, circulation, ventilation, and sweating, depending on the body temperature and the concentrations of O2 and CO2 in the blood. The lungs are represented by alveolar and blood compartments, with diffusion between them. Comparisons with experimental data from the existing literature show that the proposed model is suitable for representing transient exposure to cold and warm ambient temperatures, low concentration of O2, and high concentrations of CO2 . In the end, some results demonstrate the effect of ambient temperature on the distribution of temperature, O2, and CO2 across segments, blood, and tissues. Shivering in a cold environment reduces the concentration of O2 and increases the concentration of CO2 in the muscles, which results in increased ventilation and blood circulation. The concentration of gases in the skin depends mainly on variations in the skin's circulation with the environment, which alters the availability of O2 and the elimination of CO2 . Small variations were found in the concentrations of O2 and CO2 in the brain and lungs.